2015
DOI: 10.1186/s12987-015-0013-y
|View full text |Cite
|
Sign up to set email alerts
|

Cultured cells of the blood–brain barrier from apolipoprotein B-100 transgenic mice: effects of oxidized low-density lipoprotein treatment

Abstract: BackgroundThe apolipoprotein B-100 (ApoB-100) transgenic mouse line is a model of human atherosclerosis. Latest findings suggest the importance of ApoB-100 in the development of neurodegenerative diseases and microvascular/perivascular localization of ApoB-100 protein was demonstrated in the cerebral cortex of ApoB-100 transgenic mice. The aim of the study was to characterize cultured brain endothelial cells, pericytes and glial cells from wild-type and ApoB-100 transgenic mice and to study the effect of oxidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 56 publications
2
31
0
Order By: Relevance
“…Chloromethyl-dichloro-dihydro-fluorescein diacetate (DCFDA, Molecular Probes, Life Technologies, USA) was used for ROS detection, and 4-amino-5-methylamino-2′,7′-difluorofluorescein diacetate (DAF-FM, Molecular Probes, Life Technologies, USA) for NO detection as fluorescent probes, as described in our previous studies [39,40]. Brain endothelial cells were cultured in 96-well plates with black walls and transparent plastic bottoms (Corning, NY, USA).…”
Section: Measurement Of Reactive Oxygen Species and Nitric Oxide Prodmentioning
confidence: 99%
See 2 more Smart Citations
“…Chloromethyl-dichloro-dihydro-fluorescein diacetate (DCFDA, Molecular Probes, Life Technologies, USA) was used for ROS detection, and 4-amino-5-methylamino-2′,7′-difluorofluorescein diacetate (DAF-FM, Molecular Probes, Life Technologies, USA) for NO detection as fluorescent probes, as described in our previous studies [39,40]. Brain endothelial cells were cultured in 96-well plates with black walls and transparent plastic bottoms (Corning, NY, USA).…”
Section: Measurement Of Reactive Oxygen Species and Nitric Oxide Prodmentioning
confidence: 99%
“…Cells treated with kainate and protective drugs for 24 h were fixed with 1% paraformaldehyde for 20 min at 4 °C, permeabilized with 0.2% Triton-X100 for 10 min at 4 °C, then blocked with 3% BSA-PBS for 1 h at room temperature. Samples were incubated with rabbit anti-claudin-5 polyclonal (SAB4502981, 1:800 dilution in 3% BSA-PBS, antibody registry ID: AB_10753223; Sigma-Aldrich, USA) or rabbit anti-ZO-1 polyclonal (61-7300, 1:400 dilution in 3% BSA-PBS, antibody registry ID: AB_2533147; Invitrogen, USA) primary antibodies overnight at 4 °C, then with anti-rabbit secondary antibody conjugated with Cy3 (C2306, 1:400 dilution in PBS, antibody registry ID: AB_258792; Sigma-Aldrich, USA) and H33342 nucleus stain (1 µg/ml) for 1 h at room temperature [40]. Cells were washed with PBS between the incubations.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…decreased membrane fluidity (17,18), we hypothesized that alterations in cholesterol composition or lipid packaging in lipid rafts in response to OxLDL or atheroprone flow may alter integrin α5 distribution and/or activity. Furthermore, given that activation of NF-κB in turn activates Nod-like receptor protein 3 (NLRP3) inflammasome (19), integrin α5 would be upstream of the atheroprone flow-induced NLRP3 inflammasome (20).…”
mentioning
confidence: 99%
“…In addition, dyslipidemia may alter BBB function in AD [42], contributing to the transportation of inflammatory lipids from the blood [6]. Further, studies have found ApoB-100 protein in the membrane microdomains of primary brain endothelial cells [43, 44]. Using the LDL-receptor binding domain of apoB could be an effective way to deliver recombinant proteins across the BBB, and such an approach can be used to treat a neurodegenerative disease [45, 46].…”
Section: Discussionmentioning
confidence: 99%